HPLC methods of fexofenadine quantitative analysis in rabbits' liver - P. Yu. Mylnikov; I. V. Chernykh; A. V. Shchulkin; N. M. Popova; E. N. Yakusheva (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2020)
The investigation of pharmacokinetics of marker substrates of carrier protein P-glycoprotein (Pgp, ABCB1-protein) including fexofenadine, is one of the methods of its functional activity evaluation.The aim of the study was to work out the HPLC methods of the quantitative determination of fexofenadine in rabbits' liver.Materials and methods. The quantitative determination of fexofenadine was performed using Stayer chromatographic system (Akvilon, Russia) with UVV 104 ultraviolet detector. Reverse-phased chromatographic column Luna C18 100Å (250*4.6) was used with 5 µm granulation at 45°С. The сoncentration of fexofenadine was determined by methods of absolute peak area calibration.Results. The work was conducted in the isocratic mode. The composition of the mobile phase consisted of deionized water, acetonitrile and glacial acetic acid at the ratio of 267.4:120:4.33 brought to pH=6.7 with triethylamine. The sample processing was in the form of homogenization of 500 mg of ground liver in 500 µl of purified water with the subsequent centrifugation (1750 g) and selection of the supernatant. The proteins were precipitated by acetonitrile (2.5 ml) acidified with 375 µl of hydrochloric acid by shaking at 500 rev/min. The supernatant was transported into a separate test tube, where methylene chloride, diethyl ether and ethyl acetate were added (2 ml each). Then the solution was again shaken for 10 minutes (500 rev/min). After that, the solution was centrifuged (1750 g) and the supernatant was evaporated on a rotor-vacuum evaporator at 50°С. 300 µl of the mobile phase was added to the dry residue, and 100 µl was injected into the chromatograph. The method was validated in the linear range from 3 to 60 µg/g of fexofenadine with the acceptable intra- and intercycle accuracy, precision and stability. The method was tested on rabbits after the intravenous administration of fexofenadine at the dose of 11 mg/kg.Conclusion. The HPLC methods of fexofenadine quantitative determination in the hepatic tissue of rabbits has been worked out. It can be used for the evaluation of the functional activity of Pgp in preclinical studies.Abbreviations: Pgp - P-glycoprotein, HPLC - high performance liquid chromatography, rev/min - revolutions per minute